Respostas
respondido por:
2
Produto Notável
(a - b)² = a² - 2ab + b²
(3y^5 - 4y²)² = (3y^5)² - 2*(3y^5)*(4y²) + (4y²)²
(3y^5 - 4y²)² = 9y^10 - 24y^7 + 16y^4
*-*-*-*-*-*-*-*-*-*-*-*
16.02.2016
Sepauto - SSRC
*-*-*-*-*-*-*-*-*-*-*-*
(a - b)² = a² - 2ab + b²
(3y^5 - 4y²)² = (3y^5)² - 2*(3y^5)*(4y²) + (4y²)²
(3y^5 - 4y²)² = 9y^10 - 24y^7 + 16y^4
*-*-*-*-*-*-*-*-*-*-*-*
16.02.2016
Sepauto - SSRC
*-*-*-*-*-*-*-*-*-*-*-*
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás